The Role of Fibular Fixation in Distal Tibia-Fibula Fractures: A Meta-Analysis - Chengxin Li; Zhizhuo Li; Qiwei Wang; Lijun Shi; Fuqiang Gao; Wei Sun (Advances in Orthopedics)
Objectives. The necessity of fibular fixation in distal tibia-fibula fractures remains controversial. This study aimed to assess its impact on radiographic outcomes as well as rates of nonunion and infection. Methods. A systematic search of the electronic databases of PubMed, Embase, and Cochrane library was performed to identify studies comparing the outcomes of reduction and internal fixation of the tibia with or without fibular fixation. Radiographic outcomes included malalignment and malrotation of the tibial shaft. Data regarding varus/valgus angulation, anterior/posterior angulation, internal/external rotation deformity, and the rates of nonunion and infection were extracted and then polled. A meta-analysis was performed using the random-effects model for heterogeneity. Results. Additional fibular fixation was statistically associated with a decreased rate of rotation deformity (OR = 0.13; 95% CI 0.02–0.82, p=0.03). However, there was no difference in the rate of malreduction between the trial group and the control group (OR = 0.86; 95% CI 0.27–2.74, p=0.80). There was also no difference in radiographic outcomes of varus-valgus deformity rate (OR = 0.17; 95% CI 0.03–1.00, p=0.05) or anterior-posterior deformity rate (OR = 0.76; 95% CI 0.02–36.91, p=0.89) between the two groups. Meanwhile, statistical analysis showed no significant difference in the nonunion rate (OR = 0.62; 95% CI 0.37–1.02, p=0.06) or the infection rate (OR = 0.81; 95% CI 0.18–3.67, p=0.78) between the two groups. Conclusions. Additional fibular fixation does not appear to reduce the rate of varus-valgus deformity, anterior-posterior deformity, or malreduction. Meanwhile, it does not appear to impair the union process or increase the odds of infection. However, additional fibular fixation was associated with decreased odds of rotation deformity compared to controls.